Test Anxiety and College Students With Attention Deficit Hyperactivity Disorder. (September 2014) - Nelson, Jason M.; Lindstrom, Will; Foels, Patricia A.
Test anxiety was examined in college students with and without attention deficit hyperactivity disorder (ADHD). Results indicated that, relative to college students without ADHD, college students with ADHD reported higher total test anxiety as well as specific aspects of test anxiety, including worry (i.e., cognitive aspects of test anxiety) and emotionality (i.e., physiological aspects of test anxiety). Effect sizes were large for total test anxiety and the worry aspect of test anxiety. Nearly half of college students with ADHD reported clinically significant levels of the worry aspect of test anxiety. Females with ADHD reported higher levels of the emotionality aspect of test anxiety than did males with ADHD. Those with combined type and inattentive type ADHD did not differ on any aspect of test anxiety. Implications for assessment and intervention are discussed.